Volatile Compounds as Markers of Terroir and Winemaking Practices in Fetească Albă Wines of Romania - Ioana Cristina Bedreag (Rebigan); Ionel-Bogdan Cioroiu; Marius Niculaua; Constantin-Bogdan Nechita; Valeriu V. Cotea (Beverages, 2025)
This study evaluates the influence of terroir on the physico-chemical characteristics and aromatic profiles of Fetească albă wines from five major Romanian wine regions. By analysing key factors such as soil types, climatic conditions, and winemaking techniques, the study aims to understand their impact on wine composition and quality. The study includes the analysis of superior alcohols, fatty acids, esters, carbonyl compounds, terpenes, and 4-mercapto-4-methylpentan-2-one, which are essential in defining the aromatic complexity of the wines. The results show how fermentation conditions, temperature control, microbial activity, and oxidative exposure contribute to the evolution of these compounds, influencing the sensory profiles. Significant differences in compound concentrations were observed across the regions, with wines from Dealu Mare and Murfatlar exhibiting high ester content and aromatic complexity, while those from Dealul Bujorului and Panciu showed elevated volatile acids and aromatic alcohols, suggesting distinct fermentation dynamics. Climatic factors, such as temperature and precipitation, played a crucial role in shaping the volatile composition, with elevated temperatures in 2021 enhancing ester formation and higher alcohol production. This study demonstrates the critical role of terroir and winemaking practices in shaping the aromatic and sensory characteristics of Romanian Fetească albă wines.